Effect of Formulation of Jackfruit Seed Extract, Soybean Juice and Moringa Leaf Extract on the Amount of Lactic Acid Bacteria, Total Acid, and pH of Kalelo Yogurt as Probiotics & Supplementary Feeding for Stunting Prevention - Nur Hatijah; Melina Sari; Atika Nuswantari (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2019)
Introduction: Efforts to improve nutrition for the prevention of stunting include specific interventions with specific targets, namely pregnant women in the form of supplementary feeding for pregnant and lactating mothers. Micronutrient food sources that are still not maximized are processed including jackfruit seeds (Arthocarphus heterophilus), Soybean (Glycine max L. Mer) and Moringa oleifera leaves. Objective: Determine the right formulation in making kalelo yogurt as a probiotic and PMT to prevent stunting. Methods: Post-test only design method with yogurt formula treatment. The resulting yogurt was seen as having an effect on the amount of lactic acid bacteria, total acid and pH. The statistical analysis used was Complete Randomized Design (CRD) 3 X 2 followed by Duncan test to see the difference in mineral content of each formulation with α 0.05. Results: The number of lactic acid bacteria (LAB) ranged from 5.8 x108 to 1.8 x109, fulfilling the SNI Yoghurt standard with the highest number of F3 formulas. Total acid ranged from 11-1.2% calculated as lactic acid, fulfilling standard SNI yogurt with the highest amount of formula F2. Total solids of yoghurt formula ranged from 16.29% -16.79%, fulfilling standard SNI yogurt with the highest value of Formula F1 & F3. The pH value of Kalelo yogurt is 3.8 with a formula that has the best pH, namely F2 formula. Discussion: LAB can develop during fermentation because it uses sugar from carbohydrates in the formula. During the fermentation process, lactose derived from skim milk will be hydrolyzed by the enzyme β-galactosidase to glucose and galactose, then converted to lactic acid. The high amount of solids is caused by the addition of soybeans, jackfruit seeds which are high in sugar content. Organic acids cause a decrease in pH during the fermentation process. In addition to increasing incubation time, microbial activity is increasing and the number of microbes is increasing, resulting in pH decreasing. Conclusion: The number of lactic acid bacteria (LAB), the amount of acid calculated as lactic acid, the amount of solids and the value of PH calelo yogurt fulfills the SNI standard of yoghurt. Keywords: Provision of additional food, Yoghurt, Pregnant women, Breastfeeding mothers, Arthocarphus heterophilus, Glycinem ax L. Mer, Moringa oleifera